Modern trends in research on steel, aluminium and composite structures proceedings of the XIV International Conference on Metal Structures (ICMS2021), Poznan, Poland, 16-18 June 2021 - Gizejowski, Marian A. (Routledge, 2021)
Modern Trends in Research on Steel, Aluminium and Composite Structures includes papers presented at the 14th International Conference on Metal Structures 2021 (ICMS 2021, Pozna, Poland, 16-18 June 2021). The 14th ICMS summarised a few years' theoretical, numerical and experimental research on steel, aluminium and composite structures, and presented new concepts. This book contains six plenary lectures and all the individual papers presented during the Conference. Seven plenary lectures were presented at the Conference, including "Research developments on glass structures under extreme loads", Parhp3D - The parallel MPI/openMPI implementation of the 3D hp-adaptive FE code", "Design of beam-to-column steel-concrete composite joints: from Eurocodes and beyond", "Stainless steel structures - research, codification and practice", "Testing, modelling and design of bolted joints - effect of size, structural properties, integrity and robustness", "Design of hybrid beam-to-column joints between RHS tubular columns and I-section beams" and "Selected aspects of designing the cold-formed steel structures". The individual contributions delivered by authors covered a wide variety of topics: - Advanced analysis and direct methods of design,- Cold-formed elements and structures,- Composite structures,- Engineering structures,- Joints and connections,- Structural stability and integrity,- Structural steel, metallurgy, durability and behaviour in fire. Modern Trends in Research on Steel, Aluminium and Composite Structures is a useful reference source for academic researchers, graduate students as well as designers and fabricators.